2013
DOI: 10.1159/000351958
|View full text |Cite
|
Sign up to set email alerts
|

Adult and Near-Adult Height in Patients with Severe Insulin-Like Growth Factor-I Deficiency after Long-Term Therapy with Recombinant Human Insulin-Like Growth Factor-I

Abstract: Background: Treatment with recombinant human insulin-like growth factor-I (IGF-I) stimulates linear growth in children with severe IGF-I deficiency (IGFD). Aims: To evaluate the efficacy and safety of treatment with IGF-I in patients with severe IGFD treated until adult or near-adult height. Methods: Twenty-one children with severe IGFD were treated until adult or near-adult height under a predominantly open-label design. All patients were naive to IGF-I. Recombinant human IGF-I was administered subcutaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
7
32
1
Order By: Relevance
“…Only 10 patients have reached adult or near-adult height with a mean of less than -3.4 SDS. In patients with SPIGFD, similar adult or near-adult height was reported by Backeljauw et al [18]. In the EU IGFD Registry, of the 4 patients with a final or near adult height less than -3.4 SDS, 3 had an adult height SDS less than -5.0.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Only 10 patients have reached adult or near-adult height with a mean of less than -3.4 SDS. In patients with SPIGFD, similar adult or near-adult height was reported by Backeljauw et al [18]. In the EU IGFD Registry, of the 4 patients with a final or near adult height less than -3.4 SDS, 3 had an adult height SDS less than -5.0.…”
Section: Discussionsupporting
confidence: 76%
“…IGF-1-independent growth-promoting effects of GH, as well as the IGF-1-supporting actions of GH-dependent IGFBP-3 and ALS, are thought to be important for this difference. In a study of long-term follow-up to adult or near-adult height of patients with SPIGFD who received rhIGF-1 treatment, an increase in BMI and body fat measured by dual-energy X-ray absorptiometry was reported [18]. We found that BMI increased, approaching 0 SDS during the first year of treatment.…”
Section: Discussionmentioning
confidence: 63%
“…The number of patients is low. Long-term therapy with IGF-1 improves the adult height of patients with severe IGF-1 deficiency, although most patients do not experience sufficient catch-up growth to obtain a height in the normal range [48]. Hence, long-term IGF-1 therapy appears to be effective and relatively safe as a replacement therapy in children with SS due to severe IGF-1 deficiency.…”
Section: Etiology and Classificationmentioning
confidence: 99%
“…The response to IGF-I treatment of complete GH resistant patients, the majority Laron syndrome, has been reported [13]. From 21 patients enrolled, only 2 boys and 1 girl reached adult height within normal limits.…”
Section: The Pastmentioning
confidence: 99%